Global Mental Health: Approaches, Crisis and Impact - Bustamante, Inés (2024)
Objectives: Reflect on the evolution of global mental health (GMH) approaches in the last fifteen years and their application to policies and services, particularly in Latin-American. Describe and explain mental health impacts of the worldwide crisis and the challenges that they represent for the countries of the sub region. Topics addressed: As discourses and approaches in GMH evolved to focus more on social determinants of mental health and materialize the Sustainable Developmental Goals, communities become increasingly important in Latin-American mental health systems. However, global crises such as the COVID-19 pandemic and climate change demonstrated that the mental health of vulnerable populations, including people with mental illness and rural and indigenous populations, were disproportionately affected, exacerbating already existing inequalities in access to appropriate care and services. On the other hand, culture is a critical factor to be considered in local responses to suffering and healing processes in the face of crises. Conclusions: There is a need to prioritize equity and inclusion in GMH care. The global and regional crises that bring significant impacts on it make the affected people and communities a valuable source of knowledge and information for the development of innovative approaches and practices that promote an equitable access to health care. Therefore, it is important to recognize their voices in formulations and approaches.